The Influence Of Leadership Style And Work Motivation On Improving Employee Performance At The Turi Lamongan District Office - Shelvi Yulian Lesatari; Sabilar Rosyad; Indira Shofia Maulida (Jurnal Multidisiplin Sahombu, 2024)
Performance is the result of work in quality and quantity that can be achieved by an employee in carrying out tasks in accordance with the responsibilities given to him through strategic planning of an organization. This study aims to analyze the factors that influence employee performance at the Turi Lamngan District Office. This study uses quantitative research and data obtained from questionnaires filled out by respondents. The population obtained was 42 employees and the sample used was based on the total sample of 42 respondents. The tool used for data processing is SPSS with multiple linear regression analysis techniques. The results showed that Leadership Style and Motivation partially affect employee performance. Simultaneously, Leadership Style and Motivation partially affect employee performance. Motivation has the most dominant effect on employee performance.